The Fama of a Wife’s Family in the Heraldry of Her Husband: The Case of the Marriage of Michał Jan Gorski and Marianna Regina Wojna (Second Half of the 18th Century) - Drungilas, Jonas (Vilnius University Open Series, 2024)
This article presents an analysis of the heraldry of the Samogitian castellan Michał Jan Gorski (1717–1776), based on the 36 seals he used, three types of armorial stove tiles and two marks of patronage (at the Dominican Church of the Holy Spirit in Vilnius and the Telšiai Cathedral). These sources highlighted the development of his heraldry, while the application of semiotics and the social history approach helped reveal the motives for why the castellan used his much-admired marital coat of arms for so long.The heraldry used by Gorski may be divided into two stages. In the first (up to 1753), upon marrying Teresa Nagórska, he concentrated mostly on the manifestation of his parents’ heraldry (the type I seal). In the second stage (1753–1776), which began with his marriage to Marianna Regina Wojna and ended with the castellan’s own passing, his seals (types II to V), stove tiles and marks of patronage all featured his marital coat of arms in the centre of the two-field shield, with Gorski’s Nałęcz on the heraldic right, and the three horns of Wojna’s Trąby on the heraldic left. In addition, during the second stage the Samogitian castellan’s heraldry gradually grew more complex, where alongside the repeating decorative details (the crown on the helmet, the ducal mantle, etc.), new aspects emerged: a) an eagle’s head was used in the left corner of the shield on the type II seal, which signified rule over the county of Kėdainiai and reflected the growth of Gorski’s economic potential; b) the male heraldic ornament above the shield on the type III seal – a typical marital coat of arms element was used; c) symbols conveying the castellan’s rising status were used on the type IV and V seals: the ribbons and crosses from the Russian Order of Saint Anna (1764) and the Polish-Lithuanian Commonwealth’s Order of Saint Stanislaus (1772), and abbreviations of the offices he held.The functionality of the Samogitian castellan’s marital coat of arms (with the Wojna family’s Three Horns) even after the death of his second wife and his entering into a new marriage demonstrates its importance to Gorski, which depended on several factors. First, M. R. Wojna came from a family that his its own fama – its members in the Grand Duchy of Lithuania held high secular and religious offices in the 16th–17th centuries. Second, this family had a well known memoria (burial) place in the capital of the Grand Duchy of Lithuania – the Wojna Chapel in the Vilnius Cathedral. Third, certain factors (nine children, his request to be buried next to this wife, a longer period of mourning, perhaps, after her passing, three surviving portraits of this woman, etc.) testify that this couple shared a warm, close relationship. Fourth, Gorski’s second wife was the last representative of the Wojna family in the Grand Duchy of Lithuania. Thus, by marrying her, the Samogitian castellan not only took over the entire landholdings of this family, which significantly increased his economic potential, but also part of this family’s respectability, or fama, which he earnestly reminded other castellans of by specifically using his marital coat of arms. The latter instance shows how successful marital policy could be cleverly conveyed in the heraldry of the nobility.The Wojna family’s coat of arms in the marital heraldry of the Samogitian castellan was his social capital, becoming a part of his identity and paving the way for Gorski’s growth in status. We can see this not only from his ascent through various offices in the Duchy of Samogitia, but also from unofficial titulature, where Gorski was initially identified as the “lord of Kražiai and Salantai” before eventually being titled as count (from 1767). Thus, it is no accident that thanks to M. J. Wojna, the Gorski family featured among the top-twelve largest Lithuanian landowners according to their economic capability in the second half of the 18th century.
Keywords: seal; fama; the Gorskis; coat of arms; Salantai; marriage; the Wojnas; Vilnius; Samogitia